Pelatihan Pembuatan Konten Digital Menggunakan Aplikasi Canva Untuk Mengoptimalkan Pemasaran Produk UMKM di Desa Lab. Jambu - Tawaqqal, Akbar; Aprianto, Romi; Hidayatullah, Syarif (Universitas Mataram, 2025)
Micro, small, and medium enterprises (MSMEs) face challenges in product marketing and visibility in the digital era. This community service project aimed to enhance the digital content creation skills of MSME owners in Labuan Jambu Village, Sumbawa Regency, using the Canva application. The method employed consisted of three stages: introduction to digital content and the Canva application, hands-on content creation practice, and one-month post-training mentorship. Results showed significant improvements in participants' understanding of digital content importance, ability to produce quality content, and implementation of digital strategies in their businesses. The majority of participants successfully created relevant content without direct assistance, leading to increased customer interactions on social media and product demand from outside the region. Challenges encountered included device limitations, unstable internet connections, and difficulties in maintaining consistent application. This activity contributes to the national agenda of MSME digitalization and can serve as a model for other regions. Recommendations include developing digital infrastructure, establishing a digital MSME community, integrating training into government programs, and diversifying training materials. In conclusion, this training effectively enhanced MSMEs' digital skills, supporting local economic growth and improving competitiveness in the digital era. Keywords: MSMEs, digital content, Canva, digital marketing, economic empowerment, digitalization